Pengaruh Penggunaan Platform ChatGPT dalam Membantu Penyelesaian Tugas Sekolah Siswa (Studi Kasus SMA Fatih Billingual School) - Bakkara, Vionna Febiyola; Sari, Diana; Wulandari, Gita Maulida; Juwita, Juwita; Safita, Nia (Librarianship in Muslim Societies, 2024)
The existence of ChatGPT has brought changes in various fields including academics and education. Therefore, this study aims to describe the effect of ChatGPT technology implementation in assisting the completion of school assignments of Fatih Billingual School high school students. This study uses quantitative methods and survey methods of data collection measured using a Likert scale. The population in this study were 65 students of Teuku Nyak Arif Fatih Bilingual School. The sample in this study was 39 students obtained based on the calculation of the Slovin formula with a margin of error of 10%. The criteria for respondents are students who use ChatGPT in helping with schoolwork. The results of this study indicate that ChatGPT has an effect in helping the completion of school assignments of Teuku Nyak Arif Fatih Billingual School high school students. Based on the results of hypothesis testing, it is known that the significant value obtained is 0.008 so it can be concluded that 0.000 <0.05 (H_a  is accepted and H_0  is rejected), meaning that there is an effect of implementing the ChatGPT platform in helping students' school assignments. Therefore, ChatGPT helps in providing more relevant answers and reference information and providing a positive response on completing tasks quickly.